The effect of intra-group loans on the cash flow sensitivity of cash : evidence from Chile (2018)
We examine the effects of internal capital markets on the propensity of firms to save cash from cash flows (i.e., the cash flow sensitivity of cash). We argue that firms that are net providers of funds to related parties must maintain a higher cash flow sensitivity of cash to prevent high levels of pressure on their cash holdings in contrast to net receivers of intra-holding funds. Based on a panel of listed firms in Chile, we test this premise and examine how a firm's differences in accounts receivable and accounts payable from related companies affects its cash flow sensitivity of cash. The results confirm that firms with high levels of net loans to related companies have higher cash flow sensitivities of cash and that this relationship is strongest for firms affiliated with business groups and family-owned firms. Furthermore, providers of funds that have the propensity for high savings are those firms that are more financially constrained suggesting that the cash flow sensitivity of cash is an adequate indicator to capture financing constraints.